Metastatic Uterine Carcinosarcoma to the Orbit. Issue 6 (November 2021) - Qureshi, Sana; Patel, Nimesh A.; Patel, Nish; Ghassibi, Mark P.; Tse, David T.; Dubovy, Sander R.
Abstract : Metastases of solid tumors to the eye and ocular adnexa are rare. Herein, the authors describe the clinical, histologic, and immunohistochemical findings of a patient with a history of adenocarcinoma of the colon and a uterine carcinosarcoma (malignant mixed Müllerian tumor) who presented with proptosis and decreased vision. Positive staining with PAX-8, p16 and negative reaction for CK20 and CDX2 helped to establish the uterine origin of the metastasis. This rare case demonstrates the utility of immunohistochemical probes, especially in patients with a complex oncological history, where multiple primary sources of the metastasis are in the differential diagnosis. Abstract : Immunohistochemical stains are critical in distinguishing the histologic origin of an orbital mass in a patient with a complex oncological history presenting with proptosis and decreased vision.